2003
DOI: 10.3146/pnut.30.2.0003
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Quality Traits of the Runner-Type Peanut Cultivar Georgia Green and its Value as a Parent Compared with Florunnner1

Abstract: Georgia Green has become the dominant runner market-type peanut cultivar in the United States because of its high yield and superior disease resistance to tomato spotted wilt virus. However, the roasted peanut flavor quality of Georgia Green has not been formally reported, and questions regarding its flavor quality have been expressed by the peanut industry. The objective of this study was to compare the roasted peanut flavorqualities of Georgia Green to those of the long-time industry standard Florunner. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…From 1986 to 2000 across multiple locations in the United States, Georgia Green was found to have a similar sensory roasted peanutty flavor attribute as the peanut industry standard runner‐type cultivar, ‘Florunner’ (Norden et al, 1969). In this same long‐term study, Georgia Green was also found to be among the highest in breeding value as a parent for roasted flavor and sweet attributes as determined by the best linear unbiased prediction model (Pattee et al, 2003).…”
mentioning
confidence: 93%
“…From 1986 to 2000 across multiple locations in the United States, Georgia Green was found to have a similar sensory roasted peanutty flavor attribute as the peanut industry standard runner‐type cultivar, ‘Florunner’ (Norden et al, 1969). In this same long‐term study, Georgia Green was also found to be among the highest in breeding value as a parent for roasted flavor and sweet attributes as determined by the best linear unbiased prediction model (Pattee et al, 2003).…”
mentioning
confidence: 93%
“…In addition to the parents predicted to have positive effects on peanut flavor, two additional parents were included because of their widespread use among peanut growers: runnertype cultivar Georgia Green (Branch, 1996) and virginia-type cultivar Perry . Georgia Green was later found to have positive BLUPs of breeding value for flavor (Pattee et al, 2003) while Perry was a cultivar with negative BLUPs (Pattee et al, 2001(Pattee et al, , 2002a. The 11 parents were crossed in a half-diallel mating in the summer of 2001 in the greenhouse at the NCSU campus in Raleigh, NC.…”
Section: Methodsmentioning
confidence: 99%
“…Mean values for intensities of the roasted peanut, sweet, and bitter attributes for the 11 parents were calculated from the same set of data used to calculate BLUPs of breeding value (Pattee et al, 2003). Means were adjusted to common year and location effects and also for the effects of the covariates roast color (linear and quadratic) as an indicator of degree of roast and intensity of the fruity attribute, an indicator of poor environmental conditions pre-and post-harvest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 1986 to 2000 across multiple locations in the United States, Georgia Green was found to have a similar sensory roasted “peanutty” flavor attribute as the peanut industry standard runner‐type cultivar, Florunner. In this same long‐term study, Georgia Green was also found to be among the highest in breeding value as a parent for roasted flavor and sweet attributes as determined by the best linear unbiased prediction model (Pattee et al, 2003).…”
mentioning
confidence: 93%